The Implementation of Role of Kuttab Al-Fatih (KAF) Philosophy in Islamic Character Education - Hafnidar Hafnidar; Rosnidar Mansor; Suppiah Nichiappan (FITK UIN Walisongo, 2019)
The aim of study was to understand about the implementation of role of kuttab al fatih (KAF) philosophy in islamic character education. This research used qualitative method. The study revealed that the KAF philosophies are